1993
DOI: 10.1007/bf00180462
|View full text |Cite
|
Sign up to set email alerts
|

Delta-doping of semiconductors

Abstract: AN INVITED REVIEWThe structural, electrical and optical properties of epitaxial semiconductor layers, delta-doped with impurity atoms, are reviewed. The majority of the discussion relates to GaAs, the moststudied material, but where possible, results for Si and other semiconductors will be presented. Although the ideal situation is one of dopant atoms confined to a single atomic plane, there are several factors, such as diffusion and segregation, which broaden the profiles, and techniques to minimize these eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“…Since a FM state was also observed in Si after the implantation of nonmagnetic ions (Ar, Si) or irradiation by neutrons, some authors argued that the ferromagnetism in these alloys is due to paramagnetic defects. 15,16 Recently, an efficient way to control the doping process has been developed by means of the so-called δ-doping technique, 17 where the dopant is confined on the length scale of the lattice constant and embedded into the matrix of a host material. Such a digital magnetic heterostructure, 18 also called digital magnetic alloy (DMA), contains discrete magnetic layers (monolayers or submonolayers), which are regularly embedded into a nonmagnetic semiconductor host.…”
Section: Introductionmentioning
confidence: 99%
“…Since a FM state was also observed in Si after the implantation of nonmagnetic ions (Ar, Si) or irradiation by neutrons, some authors argued that the ferromagnetism in these alloys is due to paramagnetic defects. 15,16 Recently, an efficient way to control the doping process has been developed by means of the so-called δ-doping technique, 17 where the dopant is confined on the length scale of the lattice constant and embedded into the matrix of a host material. Such a digital magnetic heterostructure, 18 also called digital magnetic alloy (DMA), contains discrete magnetic layers (monolayers or submonolayers), which are regularly embedded into a nonmagnetic semiconductor host.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, it does not necessarily result in strong carrier confinement in the doped layer, particularly for the electrons in the highest occupied subbands and in materials with a large dielectric constant, such as SrTiO 3 . 14 We have recently shown that La-doped SrTiO 3 thin films grown by molecular beam epitaxy ͑MBE͒ exhibit lowtemperature electron mobilities that exceed those of single crystals, which indicates that these films are of very high quality. 15 In this study, we investigate the room temperature Seebeck coefficients and the electrical conductivity of both uniformly and delta-doped SrTiO 3 thin films grown by MBE.…”
mentioning
confidence: 99%
“…For Si 8-doping of GaAs (00 1) at 400°C, it is well known that Si atoms preferentially occupy Ga sites, and it has been suggested that they form two-dimensional (2D) islands [1][2][3][4][5][6][7][8]9]. Recent reflectance anisotropy spectroscopic (RAS) measurements for the deposition of Si at 400 °C onto the more As-rich c(4 x 4) surface also support this picture [14].…”
Section: Discussionmentioning
confidence: 66%
“…There has recently been significant interest in the growth and properties of 8-doping structures, which is ideal for confining the dopant atoms to a single atomic plane [2]. Silicon, one of the most studied doping impurities, has been used for 8-doping layers in growth of GaAs by molecular beam epitaxy (MBE) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%